Innovative Application of Biopolymer Keratin as a Filler of Synthetic Acrylonitrile-Butadiene Rubber NBR - Mirosława Prochoń; Anita Przepiórkowska (Journal of Chemistry)
The current investigations show the influence of keratin, recovered from the tanning industry, on the thermal and mechanical properties of vulcanizates with synthetic rubber acrylonitrile-butadiene rubber NBR. The addition of waste protein to NBR vulcanizates influences the improvement of resistance at high temperatures and mechanical properties like tensile strength and hardness. The introduction of keratin to the mixes of rubber previously blended with zinc oxide (ZnO) before vulcanization process leads to an increase in the cross-linking density of vulcanizates. The polymer materials received including addition of proteins will undergo biodecomposition in natural conditions. After soil test, vulcanizates with keratin especially keratin with ZnO showed much more changes on the surface area than vulcanizates without protein. In that aerobic environment, microorganisms, bacteria, and fungus digested better polymer materials containing natural additives.